186 SOUTHEAST ALASKA NATIVE FOODS AND THE USDA FOOD PYRAMID. Issue 1 (1st January 2007) - Slater, M. C.
Abstract : Purpose: The USDA revealed a new version of the Food Guide Pyramid in 2005. The Food Pyramid is a tool designed to be used by laypeople and health professionals in making healthy food choices and having a balanced diet. Many southeast Alaska natives still eat local fresh foods prepared in traditional ways. Often as natives move away from subsistence lifestyles, they substitute highly processed and unhealthy food choices for the fresh foods found in their backyard. Methods: Using the community-oriented primary care (COPC) model, I identified obesity as a health problem of this population. To address the poor nutrition and eating habits of the community, I obtained information from interviews with Tlingit elders about foods that are traditionally eaten by southeast Alaska natives. I modified the USDA Food Pyramid to include some of these unique foods. After consultation with a nutritionist, I decided the most useful format for a modified food pyramid guide was a miniposter that could be used as a patient handout. On one side, the miniposter has graphics of various native foods fitted into the modified USDA Food Pyramid. On the other side, foods are in bulleted lists by category. Summary: Targeted patient education material in the form of a miniposter was created and given to an on-staff nutritionist for use and distribution in the Southeast Alaska Regional Health Consortium clinic. The miniposter included many traditional Alaska native foods to encourage the choice of these foods over less healthy alternatives. Conclusions: I found that the nutritional content of many Alaska native foods is quite high, especially in comparison with processed alternatives found at the grocery store. Encouraging this patient population to choose traditional foods will lead to better overall health. A tailored version of the USDA Food Guide Pyramid will promote these choices.